2012
DOI: 10.5897/ajest11.040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rainwater harvesting and afforestation on soil properties and growth of Emblica officinalis while restoring degraded hills in western India

Abstract: Effect of rainwater harvesting (RWH) structures like Contour trench (CT), gradonie (GD), box trench (BT), V-ditch (VD) and afforestation withEmblica officinalis Gaertn (planted in August, 2005) were studied in <10%, 10-20% and >20% slopes with a view to improve soil status, plant growth, sequester carbon and rehabilitate hills for local benefits. Soil pH and EC decreased and percent soil, SOC, NO 3 -N and PO 4 -P increased in June 2010 over 2005. Enhanced soil water and nutrients in <10% slope facilitated heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Although many rainwater harvesting structures are used to conserve soil and water in degraded lands, research findings have shown variability in their effectiveness for plant growth, biomass production, restoration of degraded lands, etc. [14,21,24,27]. This result shows that the extent to which different soil and water conservation structures influence plant growth and rehabilitation on severely degraded lands needs to be further investigated, as their effect could vary depending on the severity of the degraded land, precipitation pattern, and the type of planted species used for restoration.…”
Section: Introductionmentioning
confidence: 94%
“…Although many rainwater harvesting structures are used to conserve soil and water in degraded lands, research findings have shown variability in their effectiveness for plant growth, biomass production, restoration of degraded lands, etc. [14,21,24,27]. This result shows that the extent to which different soil and water conservation structures influence plant growth and rehabilitation on severely degraded lands needs to be further investigated, as their effect could vary depending on the severity of the degraded land, precipitation pattern, and the type of planted species used for restoration.…”
Section: Introductionmentioning
confidence: 94%
“…is the common approach of rehabilitation on degraded lands [2,[7][8][9][10]. Hence, millions of tree seedlings have been planted by different afforestation/ reforestation programs in order to provide a basis for environmental improvement and increase the forest cover of the degraded lands.…”
Section: Afforestation/reforestationmentioning
confidence: 99%
“…In most cases, the afforestation/reforestation are suffering from multiple environmental factors like limited water availability, free grazing, lack of proper management, premature cutting by peasants and inadequate care [9,10,[12][13][14]. Limited water availability is the primary factor controlling plant establishment and growth in the degraded lands [7][8][9][10]12,[15][16][17]. Therefore, to insure success of establishment of tree species MHSs can be used to collect rain water in areas close to the trees.…”
Section: Afforestation/reforestationmentioning
confidence: 99%
“…La comparación de los cambios en la cobertura vegetal, producción de biomasa e índices de vegetación, es recomendable hacerlo con el sitio de entre zanjas (EZ) de los polígonos con obras y las parcelas control; los resultados del ANOVA, no muestran diferencias estadísticas signif icativas en estas variables, lo que indica que la PB en la parte media (entre zanja) del sistema zanja bordo no tiene diferencias signif icativas con el testigo, lo cual coincide con lo consignado por Cotler et al (2015). Sin embargo, en el sitio EZ, la PB es mayor en 0.22 Mg ha -1 a la mencionada en la zona de control (testigo), lo cual sugiere que existe un efecto de las zanjas bordo en la captación de agua de lluvia, no solo en la zanja sino en menor proporción en la parte media y alta del sistema como ha sido reportado por Singh et al, 2011, 2012y 2013.…”
Section: Cambios De Vegetación Entre Zanjas Y áReas De Controlunclassified
“…El establecimiento de obras en Rajasthan, India, incrementó el contenido de humedad en el suelo (CHS) con valores que fluctuaron de 14 a 24.2% comparado con parcelas testigo; en pendientes >20% y <10%, los CHS fueron 14.0 y 51.4% mayores a las zonas con pendiente de 10 a 20%. Los incrementos en la humedad del suelo favorecieron el desarrollo en altura y diámetro de la especie Emblica off icinalis Gaertn, empleada para la restauración de áreas degradadas (Singh et al, 2012). También se observó mayor contenido de humedad en el suelo en pendientes <10%, en dos periodos evaluados, con incrementos de 24.3 y 58.9 % en diciembre y de 21.1 y 29.4% en junio 2013).…”
Section: Introductionunclassified